Type a math problem
Solve for x

Steps for Completing the Square
Swap sides so that all variable terms are on the left hand side.
Subtract from both sides.
This equation is in standard form: . Substitute for , for , and for in the quadratic formula, .
Square .
Multiply times .
Multiply times .
Take the square root of .
The opposite of is .
Multiply times .
Now solve the equation when is plus. Add to .
Divide by .
Now solve the equation when is minus. Subtract from .
Divide by .
The equation is now solved.
Solve for x (complex solution)

Solve for y
Assign y
Graph
Giving is as easy as 1, 2, 3
Get 1,000 points to donate to a school of your choice when you join Give With Bing
-2x^{2}-8x+1=y
Swap sides so that all variable terms are on the left hand side.
-2x^{2}-8x+1-y=0
Subtract y from both sides.
x=\frac{-\left(-8\right)±\sqrt{\left(-8\right)^{2}-4\left(-2\right)\left(1-y\right)}}{2\left(-2\right)}
This equation is in standard form: ax^{2}+bx+c=0. Substitute -2 for a, -8 for b, and 1-y for c in the quadratic formula, \frac{-b±\sqrt{b^{2}-4ac}}{2a}.
x=\frac{-\left(-8\right)±\sqrt{64-4\left(-2\right)\left(1-y\right)}}{2\left(-2\right)}
Square -8.
x=\frac{-\left(-8\right)±\sqrt{64+8\left(1-y\right)}}{2\left(-2\right)}
Multiply -4 times -2.
x=\frac{-\left(-8\right)±\sqrt{64+8-8y}}{2\left(-2\right)}
Multiply 8 times 1-y.
x=\frac{-\left(-8\right)±\sqrt{72-8y}}{2\left(-2\right)}
x=\frac{-\left(-8\right)±2\sqrt{18-2y}}{2\left(-2\right)}
Take the square root of 72-8y.
x=\frac{8±2\sqrt{18-2y}}{2\left(-2\right)}
The opposite of -8 is 8.
x=\frac{8±2\sqrt{18-2y}}{-4}
Multiply 2 times -2.
x=\frac{2\sqrt{18-2y}+8}{-4}
Now solve the equation x=\frac{8±2\sqrt{18-2y}}{-4} when ± is plus. Add 8 to 2\sqrt{18-2y}.
x=-\frac{\sqrt{18-2y}}{2}-2
Divide 8+2\sqrt{18-2y} by -4.
x=\frac{-2\sqrt{18-2y}+8}{-4}
Now solve the equation x=\frac{8±2\sqrt{18-2y}}{-4} when ± is minus. Subtract 2\sqrt{18-2y} from 8.
x=\frac{\sqrt{18-2y}}{2}-2
Divide 8-2\sqrt{18-2y} by -4.
x=-\frac{\sqrt{18-2y}}{2}-2 x=\frac{\sqrt{18-2y}}{2}-2
The equation is now solved.
-2x^{2}-8x+1=y
Swap sides so that all variable terms are on the left hand side.
-2x^{2}-8x=y-1
Subtract 1 from both sides.
\frac{-2x^{2}-8x}{-2}=\frac{y-1}{-2}
Divide both sides by -2.
x^{2}+\frac{-8}{-2}x=\frac{y-1}{-2}
Dividing by -2 undoes the multiplication by -2.
x^{2}+4x=\frac{y-1}{-2}
Divide -8 by -2.
x^{2}+4x=\frac{1-y}{2}
Divide y-1 by -2.
x^{2}+4x+2^{2}=\frac{1-y}{2}+2^{2}
Divide 4, the coefficient of the x term, by 2 to get 2. Then add the square of 2 to both sides of the equation. This step makes the left hand side of the equation a perfect square.
x^{2}+4x+4=\frac{1-y}{2}+4
Square 2.
x^{2}+4x+4=\frac{9-y}{2}